2009
DOI: 10.1097/meg.0b013e328326cacb
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported symptoms during an ulcerative colitis flare: A Qualitative Focus Group Study

Abstract: It has been assumed that the symptoms measured in disease activity indices for ulcerative colitis reflect those symptoms that patients find useful in evaluating the severity of a disease flare. In this qualitative focus group study, we aimed to identify which symptoms are important to patients and to compare these symptoms with a comprehensive list of commonly measured symptoms to determine/evaluate whether the patient-reported important symptoms are represented in current disease activity indices for ulcerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 22 publications
2
32
0
2
Order By: Relevance
“…Ulcerative colitis (UC) affects approximately 220 per 100 000 patients in the United States and is associated with painful and unpredictable symptoms, undesirable psychosocial consequences and disability, particularly during periods of disease flare . Medical treatment is focused on prolonging remission and reducing exposure to environmental triggers of flare .…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC) affects approximately 220 per 100 000 patients in the United States and is associated with painful and unpredictable symptoms, undesirable psychosocial consequences and disability, particularly during periods of disease flare . Medical treatment is focused on prolonging remission and reducing exposure to environmental triggers of flare .…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analyses 5-22: other deterministic sensitivity analyses (medical and surgical options) Table 83 presents the results of the remaining deterministic sensitivity analysis (analyses [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Assessment Group Model Resultsmentioning
confidence: 99%
“…Patients did not have to describe precisely the intensity of their symptoms (e.g., intensity of abdominal pain), or amount (e.g., amount of blood in their stool), but they were only asked if such a symptom is for them present. The included symptoms of ulcerative colitis were based on the Qualitative Focus Group Study by Waljee et al [24], as they identified which symptoms of ulcerative colitis are in fact important for patients, and they compared these symptoms with commonly measured ones to determine whether the patient-reported important symptoms are represented in current disease activity indices for ulcerative colitis. In the referred study, among other symptoms which are reported by patients, as recognized by them, but at the same time, which are not included to used indices of disease activity, there were: presence of mucus in stool, constipations and flatulence [24].…”
Section: Disease Symptomsmentioning
confidence: 99%